ANALISIS PERILAKU KENAKALAN REMAJA PADA SISWA MELALUI PENDEKATAN BEHAVIORAL; STUDI LITERASI - Fadhiilah Fatmasari; Futikhatun Karomah; Endang Rifani (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2024)
Juvenile delinquency is a behavioral mismatch or a behavior that is far from social relations and violates norms, religion, and legal rules or authorities that apply in society. In solving the problem of juvenile delinquency, a solution or counseling technique provided by the BK teacher to students is needed. In this juvenile delinquency problem, the case resolution uses a behavioral approach. The behavioral approach is a rapidly developing and very well-known behavioral therapy approach, because it meets the principles of simplicity, is easy to understand and apply, and there is an emphasis on positive behavior. The research in this article was compiled using a literacy study method that collected data through previous research. The subjects that can be involved in this research are between adolescents or students and guidance counseling teachers related to using behavioral approaches as a solution. The purpose of this research is to find out how the use of behavioral approaches in dealing with juvenile delinquency problems. The results showed that there is still a lot of juvenile delinquency that occurs, both in the school environment and society, which is largely due to the lack of parental attention and love at home. By applying the behavioral approach, it is hoped that it can reduce the juvenile delinquency that occurs. Keywords: juvenile delinquency, behavioral approach, behaviors